Analysis of Orphenadrine Citrate in Various Chiral Stationary Phases: A Comparative Study - Raikar, Prachi; Gurupadayya, Bannimath M.; Subramanyam, Sripuram; Srinivasu, Gunnam (Current Chromatography, 2020)
Background: Polysaccharide based chiral stationary phases (CSPs) were used to perform enantiomeric separation of Orphenadrine Citrate by Ultra-Fast Liquid Chromatography (UFLC) technique. Trials were conducted using the polar mode, reverse phase mode and normal phase mode. Amylose and Cellulose-based CSPs were used for the same. Materials and Methods: Eight Amylose-based CSPs and four Cellulose-based CSPs were used in the reverse phase mode. Five Amylose-based CSPs and two Cellulose-based CSPs were used in polar mode. The only Cellulose-based CSP used in the normal phase mode could effectively separate Orphenadrine Citrate enantiomers with a good resolution. Results and Discussion: Successful enantioseparation was obtained using Chiralcel OD-H containing Cellulose tris (3, 5- dimethylphenylcarbamate) as a chiral selector and n-hexane: Ethanol: Diethylamine (95: 05: 0.1, v/v/v) as the mobile phase. The developed method was validated in accordance with ICH guidelines (Q2R1). Conclusion: The proposed objectives were successfully accomplished as the developed method could effectively resolve Orphenadrine Citrate enantiomers.
Keywords: cellulose-based CSPs